Baicalein as a potent antifungal agent against Candida albicans: synergy with fluconazole and sustainable production through probiotic-mediated bioconversion - Zhai, Hang; Zeng, Jialing; Ma, Xiaonan; Wang, Fuju; Xu, Wei; Song, Ming; Xu, Weizhuo (Frontiers in Microbiology, 2025)
Fungal infections, particularly those caused by Candida albicans, represent a significant global health concern, with drug resistance and biofilm formation posing considerable challenges to effective treatment. Baicalein, a flavonoid derived from baicalin found in Scutellaria baicalensis, has demonstrated considerable antifungal efficacy. Moreover, the combination of baicalein and fluconazole demonstrated a notable synergistic effect. Given the restricted natural accessibility of baicalein, Lactobacillus rhamnosus has been identified as a microbial agent capable of converting baicalin to baicalein via whole-cell catalysis. This process has been shown to achieve a molar yield of 66% at a substrate concentration of 4 g/L under optimized conditions. In addition to the antifungal properties of baicalein, L. rhamnosus demonstrated intrinsic antifungal activity against C. albicans. The combination of baicalein and L. rhamnosus resulted in a notable enhancement in the inhibition of C. albicans growth. The key enzyme responsible for baicalin hydrolysis, β-glucuronidase (LrGUS2), is indicative of the biotransformation potential of L. rhamnosus. This study demonstrates the potent antifungal activity of baicalein, its synergistic effects with fluconazole, and the ability of L. rhamnosus to efficiently convert baicalin into baicalein. These findings highlight the potential for developing baicalein as a novel antifungal agent, particularly in combination therapies for resistant C. albicans infections, and provide a scalable, safe method for baicalein production using probiotics.